Immunosuppressive effect of a non-proteinogenic amino acid from Streptomyces through inhibiting allogeneic T cell proliferation. Issue 6 (3rd June 2019) - Yashiro, Takuya; Sakata, Fumiya; Sekimoto, Takahiro; Shirai, Tomohiro; Hasebe, Fumihito; Matsuda, Kenichi; Kurosawa, Sumire; Suzuki, Shodai; Nagata, Kazuki; Kasakura, Kazumi; Nishiyama, Makoto; Nishiyama, Chiharu
ABSTRACT: The immunosuppressive activity of myriocin (ISP-1), a lead compound of fingolimod (FTY720), is derived from its 2-amino-1, 3-propandiol structure. A non-proteinogenic amino acid, (2 S, 6 R )-diamino-(5 R, 7)-dihydroxy-heptanoic acid (DADH), that contains this structure, was recently identified as a biosynthetic intermediate of a dipeptide secondary metabolite, vazabitide A, in Streptmyces sp. SANK 60404; however its effect on adaptive immunity has not yet been examined. In this study, we examined whether DADH suppresses mixed lymphocyte reaction using mouse bone marrow-derived dendritic cells (BMDCs) and allogeneic splenic T cells. Although T cell proliferation induced by cross-linking CD3 and CD28 were not suppressed by DADH unlike ISP-1, the pre-incubation of BMDCs with DADH but not ISP-1 significantly decreased allogeneic CD8 + T cell expansion. Based on these results, we concluded that DADH suppresses DC-mediated T cell activation by targeting DCs. Graphical abstract: : DADH suppresses T cell proliferation activity of dendritic cells, whereas ISP-1 targets T cells directly.